Malnutrition syndrome as a prognostic risk factor for intestinal suture failure in elderly and senile patients with gastric and duodenal ulcer perforation - Danyliuk, M. B.; Zavgorodnyi, S. M.; Kubrak, M. A.; Chemeris, Y. O.; Данилюк, Михайло Богданович; Завгородній, Сергій Миколайович; Кубрак, Михайло Анатолійович; Чемерис, Юлія Олександрівна (My University, 2024)
Objective. To study the effect of malnutrition syndrome on the risk of intestinal suture failure in elderly and senile patients with gastric and duodenal ulcer perforation. Materials and methods. The results of treatment of 100 elderly and senile patients with perforated gastric and duodenal ulcers who were operated on urgently were analysed. According to the results of previous studies and the analysis of literature sources, the Edmonton Frail scale was used as the basis for the diagnosis of senile asthenia syndrome. Results. On the basis of the assessment of the presence of senile asthenia syndrome, patients of the total sample were divided into two groups: A – 42 (42.0%) patients without senile asthenia syndrome; B – 58 (58.0%) patients with detected senile asthenia syndrome. Determination of total protein and albumin levels confirmed the presence of malnutrition syndrome in patients with senile asthenia syndrome: group A – 70.93 (66.00; 76.00) and 34.61 (31.50; 38.20) g/l, respectively; group B – 61.35 (55.00; 70.00) g/l (p = 0.0009, U = 224.0) and 29.75 (24.70; 35.70) g/l (p = 0.0072, U = 268.0). The analysis of the incidence of postoperative complications revealed that, although the diagnoses, prevalence of inflammation and volume of surgical intervention in the groups were comparable, the incidence of intestinal suture failure in group B was higher – 11 (19.0%) patients than in group A – 2 (4.8%) patients (p = 0.0386, U = 1045.0). The obtained results confirm that the presence of malnutrition syndrome can be considered a prognostic factor for the development of such a complication as intestinal suture failure. Conclusions. The statistically significant effect of malnutrition syndrome on the incidence of intestinal sutures failure was determined: 4.8% – in patients without senile asthenia; 19.0% – in patients with senile asthenia (p = 0.0386, U = 1045.0). Determination of the syndrome of senile asthenia before surgery in elderly and senile patients will make it possible to choose the optimal volume of surgical intervention and timely start corrective therapy in the early postoperative period to reduce the incidence of surgical postoperative complications and improve the quality of treatment of this category of patients.
Keywords: malnutrition; perforation; senile asthenia syndrome; peritonitis